Households and Financialization in Europe Mapping Variegated Patterns in Semi-Peripheries - Mikuš, Marek; Rodik, Petra (Taylor & Francis, 2021)
Households and Financialization in Europe develops a processual, relational and critical transdisciplinary approach to household financialization in Europe, utilizing a range of national and local case studies. It does so by drawing on debates in Marxist, feminist and radical IPE, anthropology and other fields. The book explores the household as simultaneously a micro-level social institution specializing in social reproduction, distribution and other activities; a building bloc of larger economic and social structures; and an object of multiple systems of power/knowledge. Putting this conceptualization to use in original research, the authors identify geographically and historically situated ways in which financialization transforms households and their relationships with the wider economy and society. The book traces these transformations in case studies of variegated financialization in Eastern and Southern European (semi-) peripheries where households have faced particularly severe financial issues since the global financial crisis, such as over-indebtedness and asset devaluation. Key themes recurring throughout the book include: the key role of housing in household financialization, the co-constitutive relationship between financialization and social and spatial inequalities, specific patterns in the relations of financial actors and households in semi-peripheries, and the implications of semi-peripheral forms of real and financial accumulation for household financialization. With its transdisciplinary approach, this book will be of great interest to students and scholars of finance, financialization, household economics, international and global political economy, uneven development, economic anthropology, and economic sociology.